Comparative study of phrenic and partial ulnar nerve transfers for elbow flexion after upper brachial plexus avulsion: A retrospective clinical analysis. Issue 9 (September 2018) - Liu, Yuzhou; Zhuang, Yongqing; Yu, Hu; Xiong, Hongtao; Lao, Jie
Summary: The widely used nerve transfer sources for elbow flexion in patients with upper brachial plexus avulsion (UBPA) include partial ulnar nerve, phrenic nerve, and intercostal nerves. A retrospective review of 21 patients treated with phrenic and partial ulnar nerve transfers for elbow flexion after UBPA was carried out. In the phrenic nerve transfer group, the phrenic nerve was transferred to the anterolateral bundle of the anterior division of the upper trunk; in the partial ulnar nerve transfer group, one fascicle of the ulnar nerve was transferred to the biceps branch. The British Medical Research Council (MRC) grading system, angle of elbow flexion, electromyography (EMG), and the Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire scoring were used to evaluate the recovery of elbow flexion at least 3 years postoperatively. The efficiency of motor function in phrenic nerve transfer group was 82%, whereas it was 80% in partial ulnar nerve transfer group. The outstanding rates of angle of elbow flexion were 64% and 70% in phrenic and partial ulnar nerve transfer groups, respectively. The DASH scores after surgery were significantly lower than those before surgery in the two groups. There was no statistical difference between the two groups in the changes of DASH scores before and after surgery. Both of phrenic and partial ulnar nerve transfers had good prognosis for elbow flexion in patients with UBPA.